Past, present and (possible) future of biofouling regulatory instruments within the international marine environmental protection framework - Mar Santos-Simón; Ainhoa Fernández-García de la Yedra; Maren Ortiz-Zarragoitia; Agnese Marchini (Environmental Sciences Europe)
Abstract Marine biofouling is associated with remarkable impacts for many maritime industries and is linked with major environmental concerns. Although national biofouling regulations have been issued by a few countries in the recent past, these remain isolated initiatives. At a global scale, even if biofouling undeniably accounts for important costs and risks, there is currently no international legally binding framework on it. This work focuses on the evolution of international marine environmental protection legislation and analyzes existing regulatory instruments linked to the matter, with particular emphasis on the European legislation and other few regional in-force regulations on biofouling, and eventually focussing on the sector of recreational boating. Finally, the main gaps and challenges for the development of a regulatory framework on biofouling are identified and listed, along with the major learnings and proposals derived from the experimental outcomes of recent works, to provide an integrative tool for suitable antifouling selection.